Sacramentality in Hinduism and Christianity: A Comparative Theological Approach - D'Almeida, Anil (Concilium, 2025)
This article explores the concept of sacramentality within Hinduism, particularly through the lens of the Rāmlīlā tradition. By applying the comparative theological method of Francis X. Clooney, the study highlights how Rāmlīlā serves as a performative encounter with the divine, inviting participants into sensory experiences. The analysis reveals that this tradition, rooted in the epic Rāmcaritmānas, fosters an integrated worldview where physical and spiritual realms are intertwined, providing a direct means of experiencing the sacred. Ultimately, the article draws connections to Christian traditions, emphasizing the importance of sensory engagement, popular devotions, and the performative nature of liturgy in deepening faith.